Intangible assets in Germany: Analysis of the German stock market index DAX and a survey among the German Certified Public Accountants. Issue 2 (2nd September 2014) - Frey, Hannes; Oehler, Andreas
Abstract : Purpose: – Intangible assets are regarded as the future value drivers of company performance. However, hardly anything is known about the actual importance and influence of intangible assets. The purpose of this paper is to fill this gap, so the authors analyse the German stock market index DAX and accomplish a survey among the German Certified Public Accountants (CPAs) concerning intangible assets. Design/methodology/approach: – In a first step, the authors analyse the balance sheet data and the corresponding notes of the companies with regard to reported values of intangible assets and applied valuation methods. The sample period covers the years from 2005 to 2008. In a second step, the authors analyse the statements of the German CPAs with regard to intangible assets. The authors sent a standardised questionnaire to all 180 offices of the top ten German auditing firms. Findings: – The results indicate that intangible assets have gained in importance, while information on valuation methods is still scarce. According to the German CPAs, the current influence of intangible assets on company performance is on a high level and even will increase during the next few years. The mostly used valuation approach for the fair value measurement of patented technologies is the income approach. Furthermore, the accounting standards leave room for accounting policy – a result which casts doubt on the reliability of financial statements. Originality/value: – For the first time not only annual balance sheet data but also corresponding notes regarding intangible assets are analysed. The findings are connected with a survey of an expert group for the valuation of intangibles.